The Covid-19 Disease in Pediatric Cancer Patients: A Single Center Experience - Özlem Terzi; Hüseyin Avni Solgun; Nuran Karabulut; Sibel Tekgündüz; Fatma Sek; Cengiz Bayram; Ali Ayçiçek (Tropical Health and Medical Research, 2022)
Children with cancer can have a severe disease when infected with respiratory viruses. In this study, we aimed to understand the clinical course and outcomes of SARS-CoV-2 infection in children with cancer. Data evaluated about laboratory-confirmed SARS-CoV-2 infections in sixty-three children (<18 years) with cancer between 01.06.2020 - 01.08.2021 were retrospectively reviewed. Data for demographics, oncological diagnosis, clinical course, and cancer therapy details were collected. Primary outcomes were disease severity and modification to cancer-directed therapy. The median (range) age was 7.6 ± 5.3 (0-18) years, and the most common underlying diagnosis was leukemia (74.6%). The most common symptom was fever (67.7%), and most patients had symptoms (70%). The mild disease was most common (60.3%). During Covid-19 infection, disease severity increased 23 times (p=0.003) in those with fever and 4.083 (p=0.045) in those with neutropenia. It was observed that the severity of the disease increased 2.589 times as CRP increased (p<0.001). However, few patients (9.5%) were admitted to the intensive care unit. Five patients died, but none of the deaths could be attributed to Covid-19 alone. Most patients did not experience chemotherapy treatment interruption (57%). When interruption did occur, this duration was 13.9±14.3 (1.0-60.0) days. In this cohort of pediatric oncology patients, nearly 43% of patients who had Covid-19 were their chemotherapy interrupted. Future studies will only reveal the final effect of the pandemic on childhood cancer.